The effect of high dose digoxin on cytokines in healthy dogs - Haluk Dülger; Mehmet Ramazan Şekeroğlu; Beyhan Eryonucu; Tevfik Noyan; Süleyman Alici (Mediators of Inflammation)
Background: Tumor necrosis factor (TNF)-α and interleukin (IL)-1β are pro-inflammatory cytokines, causing myocardial dysfunction and a negative inotropic effect. The drugs used to treat heart failure affect the production of cytokines. Digoxin, on which this study was focused, is one of the drugs for the treatment of heart failure.